Translation, cultural adaptation, and psychometric validation of the Persian version of the children's trust in general nurses’ scale - Jamalodin Begjani; Armin Zareian; Mohammad Mehdi Rajabi (Nursing and Midwifery Studies)
Background: Trust serves as a fundamental element in promoting and maintaining effective communication between nurses and patients. The existing literature on children's trust in nurses is limited, largely due to the absence of validated and reliable measurement instruments.Objectives: This study aimed to translate the Children’s Trust in General Nurses Scale (CTGNS) into Persian and to evaluate its psychometric properties.Methods: This methodological study involved 450 pediatric patients referred to the Children’s Medical Center Hospital from March to June 2024. Participants were selected using convenience sampling. A forward-backward translation process was employed to ensure both linguistic and cultural equivalence. Face validity was assessed qualitatively, while content validity was evaluated through qualitative expert opinions and quantitatively using the content validity index (CVI) and modified kappa statistic. Construct validity was assessed using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). Additionally, convergent and discriminant validity were examined. Reliability was determined using Cronbach’s alpha coefficient, intraclass correlation coefficient (ICC), and standard error of measurement (SEM). Data analysis was conducted using SPSS version 26, Smart PLS version 3.2.8, and LISREL version 8.8.Results: The scale demonstrated robust psychometric properties, confirming face, content, convergent, and discriminant validity. EFA revealed three factors among the nine items. The CFA supported the model derived from EFA. The scale exhibited adequate internal consistency, with a Cronbach's alpha of 0.72. Reliability was further corroborated by an ICC of 0.83.Conclusion: The Persian version of the CTGNS is a valid and reliable tool for assessing children’s trust in nurses.